Carotid Endarterectomy in a Patient With Type 2 Myocardial Infarction During Preparation for Surgery: A Case Report. Issue 4 (15th August 2019) - Landesberg, Giora; Salem, Ronza; Avraham, Eyal; Avidan, Alexander; Karmeli, Ron
Abstract : We present a patient who was admitted for carotid endarterectomy due to tight carotid stenosis and recent amaurosis fugax. His medical history included significant coronary artery disease with stable angina pectoris, hypertension with wide pulse pressure, chronic renal failure, and anemia. During preparation for surgery, the patient developed type 2 myocardial infarction with prolonged chest pain, ST depressions on electrocardiogram, and significant troponin elevations. The patient posed a serious clinical dilemma whether to continue with surgery despite the type 2 myocardial infarction or postpone the surgery. We discuss the diagnostic tests and the decision-making processes that guided us in the preoperative period.